A Rare Cause of Chronic Hip Pain From PEComa: An Aggressive Mesenchymal Sarcoma - Samender Randhawa MD; Jessica Pinsker BS; Madhurya Amirapu MBBS; Metlapalli Venkata Sravanthi MBBS; Prashanth Ashok Kumar MBBS; Komal Akhtar MD (SAGE Publishing, 2022)
Perivascular epithelioid cell tumors (PEComas) are related to the tuberous sclerosis complex (TSC) and are commonly benign. When malignant, they can be aggressive with local invasion and metastatic spread. Conventional PEComas do not have TFE3 gene rearrangement and are associated with TSC with a preference for an occurrence at a younger age. We report a case of a young male who had progressive chronic hip pain and was found to have a TFE3 -associated PEComa in his pelvic region.